2008
DOI: 10.1186/1471-2229-8-15
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of non-TIR NBS-LRR resistance gene analogs in Musa acuminata Colla: Isolation, RFLP marker development, and physical mapping

Abstract: Background: Many commercial banana varieties lack sources of resistance to pests and diseases, as a consequence of sterility and narrow genetic background. Fertile wild relatives, by contrast, possess greater variability and represent potential sources of disease resistance genes (R-genes). The largest known family of plant R-genes encode proteins with nucleotide-binding site (NBS) and C-terminal leucine-rich repeat (LRR) domains. Conserved motifs in such genes in diverse plant species offer a means for isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 57 publications
(79 reference statements)
1
44
0
Order By: Relevance
“…Among defense-related genes, those encoding nucleotide-binding site leucine-rich repeat proteins were found to be less represented in the Musa sequence (89 genes) compared to Oryza sativa (464 genes) and Vitis vinifera (459 genes) (D'Hont et al 2012). In banana an extensive isolation of resistance genes has been done (Miller et al 2008;Peraza-echeverria et al 2008). PTI (pathogen-triggered immunity)-related genes like chitin elicitor-binding protein (CeBiP) and the chitin elicitor receptor kinase (CeRK1), important components of the plant signaling pathway that recognizes chitin oligosaccharide, are expressed more in resistant cultivar than susceptible against Foc TR4 (Li et al 2012).…”
Section: Plant Recognitionmentioning
confidence: 99%
“…Among defense-related genes, those encoding nucleotide-binding site leucine-rich repeat proteins were found to be less represented in the Musa sequence (89 genes) compared to Oryza sativa (464 genes) and Vitis vinifera (459 genes) (D'Hont et al 2012). In banana an extensive isolation of resistance genes has been done (Miller et al 2008;Peraza-echeverria et al 2008). PTI (pathogen-triggered immunity)-related genes like chitin elicitor-binding protein (CeBiP) and the chitin elicitor receptor kinase (CeRK1), important components of the plant signaling pathway that recognizes chitin oligosaccharide, are expressed more in resistant cultivar than susceptible against Foc TR4 (Li et al 2012).…”
Section: Plant Recognitionmentioning
confidence: 99%
“…In recent studies molecular markers were identified for banana classification (Wong et al 2002;Buhariwalla et al 2005;Santos et al 2005;Ruangsuttapha et al 2007;Swangpol et al 2007;Miller et al 2008), but the usefulness of these markers depends on (a) the distribution pattern of the markers on the chromosomes; (b) the genetic and structural location of these markers on conserved regions of different genomes; and (c) the possibility of chromosomal rearrangements between potential crossing parents in the chromosome regions of economically important traits (Pillay et al 2004). In order to determine small chromosomal rearrangements such as translocations and inversions or even the position of a smaller DNA sequence a more refined methodology based on single copy fluorescent in situ hybridization (FISH) is required.…”
Section: Introductionmentioning
confidence: 99%
“…CC-NBS-LRR-type proteins, the largest group of non-TIR-NBS-LRR proteins, can be found in both dicotyledons and monocotyledons. As with TNL, genome analyses of different plants (A. thaliana, Populus, Oryza sativa) have shown the remarkable structural diversification of this group [34]. In rice, genes encoding proteins with two NBS domains (CC-NBS-NBS-LRR) were identified [35].…”
Section: The Classification Of Nbs-lrr Proteinsmentioning
confidence: 99%